Rayu : A Competitive Strategy Model of Wood Craft Business in Soloraya Post Covid-19 Pandemic - Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Objective: The woodcraft business sector in Soloraya has promising opportunities, but currently, the number of businesses is decreasing due to the Covid-19 pandemic. This research aims to analyze the effect of market orientation and product innovation on marketing performance mediated by competitive strategy. Research Design & Methods: This study uses a quantitative method surveying 120 woodcraft businesses in Soloraya. The sample was obtained using a purposive sampling method with the business's criteria for more than 5 years and was analyzed using the Structural Equation Model (SEM) using PLS to obtain comprehensive results. Findings: The results show that market orientation and product innovation positively and significantly affect competitive strategy and business performance. Competitive strategy can also mediate the effect of market orientation and product innovation on marketing performance. Implications & Recommendations: Market orientation implements a marketing concept that can provide superior value to consumers. The competitive strategy is intended to maintain a level of gain and a sustainable position when facing competition. When increasing the competitive strategy, it needs to analyze the strengths and weaknesses of the business, so when determining the price, form, and quality as a competitive advantage, the competitors cannot be imitated perfectly. Contribution & Value Added: This competitive strategy model provides the enterprise with more significant opportunities to expand market share and rise from adversity due to the Covid-19 pandemic to continue to exist in the industry. In addition, this model can be applied to other areas so that this type of business does not experience a shortage of supplies.